IMPLEMENTATION OF HEAVY EQUIPMENT SERVICE MONITORING SYSTEM AT PT. SENTRA KARYA LOGISTIK - Ely Nuryani; Sutanto Sutanto; Huswatun Hasanah; Irma Yunita Ruhiawati; Fikri Nugraha (Jurnal Sistem Informasi, 2025)
The service monitoring system is a monitoring process of the periodic service schedule for vehicle units or heavy equipment with the aim that no heavy equipment misses the periodic service schedule. Currently, the monitoring service system is widely used by large companies engaged in the logistics sector. PT. Sentra Karya Logistik is a company engaged in logistics and heavy equipment rent. PT. Sentra Karya Logistik has several problems in the process of monitoring heavy equipment services. These problems include checking the hours meter (HM) of heavy equipment which is still done manually by asking directly to each operator, recording and searching monitoring service data still using Microsoft Excel so that it takes a long time and there is no notification of heavy equipment that has entered service time so that many heavy equipment often miss their regular service schedule. Based on the above problems, a web-based heavy equipment monitoring service system was created using the waterfall method because this method uses a systematic and sequential approach. With system modeling using the Unified Modeling Language (UML). The purpose of this research is to create a system that can simplify the process of recording and searching monitoring service data and can provide notifications for each heavy equipment that is approaching its periodic service time. The result of this research is the Heavy Equipment Monitoring Service System at PT. Sentra Karya Logistik.   Keywords: Heavy Equipment, Monitoring Service, Monitoring Service System, Waterfall Method.